2015
DOI: 10.1177/1933719114536472
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Tumor Necrosis Factor-α and Tumor Necrosis Factor Receptor 1/Tumor Necrosis Factor Receptor 2 System in Mononuclear Cells Recovered From Peritoneal Fluid of Women With Endometriosis at Different Stages

Abstract: During endometriosis, a breakdown occurs in endometrial and peritoneal homeostasis caused by cytokine-induced cell proliferation and dysregulation of apoptosis. We studied tumor necrosis factor (TNF)-a, TNF receptor (TNFR) 1, and TNFR2 gene expression at both messenger RNA (mRNA) and protein levels in peritoneal fluid (PF) mononuclear cells (PFMCs), the percentages of these cells bearing the same markers, and soluble TNF-a (sTNF-a) values in PF of 80 women with endometriosis. We found that TNFR1 mRNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 24 publications
1
37
0
3
Order By: Relevance
“…However, some studies reported higher peripheral levels of IL-6 [27], IL-8 [28], TNF-α [29], and interferon-γ [27] in patients with endometriosis than in controls. A study evaluating the role of proinflammatory cytokines in endometriosis found that soluble TNF-α values were decreased from minimal stages to severe stages of the disease; however, membrane TNF-α levels increased as the disease worsened [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies reported higher peripheral levels of IL-6 [27], IL-8 [28], TNF-α [29], and interferon-γ [27] in patients with endometriosis than in controls. A study evaluating the role of proinflammatory cytokines in endometriosis found that soluble TNF-α values were decreased from minimal stages to severe stages of the disease; however, membrane TNF-α levels increased as the disease worsened [23].…”
Section: Discussionmentioning
confidence: 99%
“…regulatory T cells, macrophages, and NK cells) and related cytokine patterns may address the response against the foci. The breakdown of peritoneal homeostasis may allow the escaping from immune surveillance of the endometriotic cells, which can implant and proliferate to avoid the apoptotic pathways (Sturlese et al 2011, Salmeri et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Accordingly, the breakdown of peritoneal homeostasis can keep the endometriotic cells from escaping from immune surveillance; thereafter, endometriotic cells can implant and proliferate avoiding the apoptotic pathways. 43,44 Our findings should thus encourage future prospective research on these 3 chemokine axes among endometriosis lesions using different and quantitative methods of assessing their activity levels, such as primary cell culture, polymerase chain reaction, and transwell migration assays. This should not only consider the peritoneal implantation of endometriotic stromal cells but also take into account DIE and the endometriotic lesions affecting the PSLN.…”
Section: Discussionmentioning
confidence: 92%